EFEKTIVITAS EKSTRAK DAUN JERUK NIPIS (Citrus aurantifolia) MENGOBATI IKAN NILA (Oreochtomis niloticus) YANG TERINFEKSI BAKTERI Aeromonas hydrophilla - anggi, anggi; Anjelita Pasaribu, Tania; Hutabarat, Naomi; Kurniawan, Ardiansyah; Febrianti, Dwi (Biosel Biology Science and Education, 2023)
Tilapia is one of the freshwater fish that is widely cultivated because of its economic value and also one of the fishery commodities that is quite popular and very popular with the public because it is a superior commodity of freshwater fish. Tilapia has a comparative advantage because of its distinctive and savory meat flavor with a fairly high omega and nutritional content, fast growth. The obstacles that are often experienced by farmers are bacteria, viruses, and fungi. One of them is MAS (Motil aeromonas septicemia) disease caused by Aeromonas hydrophilla bacteria. The way of overcoming which is often done by cultivators is by means of treatment with chemicals which if given on a larger scale will be at high risk. This research aims to provide an alternative in treating fish infected with Aeromonas hydrophilla bacteria with herbal ingredients, one of which is lime leaf extract.  In this study, the sample of Tilapia used was 80 fish measuring 6-8 cm while the dose of bacteria used was 0.1ml / tail, the fish was injected in the intramuscular part of the fish. In this study, the observations observed were clinical symptoms, cure rate, survival and feeding response